Problems in Quantum Mechanics with Solutions - d'Emilio, Emilio; Picasso, Luigi E.; SpringerLink (Online service) (Milano : Springer Milan, 2011)
242 solved problems of several degrees of difficulty in nonrelativistic Quantum Mechanics, ranging from the themes of the crisis of classical physics, through the achievements in the framework of modern atomic physics, down to the still alive, more intriguing aspects connected e.g. with the EPR paradox, the Aharonov--Bohm effect, quantum teleportation.
Classical Systems -- Old Quantum Theory -- Waves and Corpuscles.-States, Measurements and Probabilities.-Representations. One-Dimensional Systems -- Time Evolution. Angular Momentum -- Changes of Frame -- Two and Three-Dimensional Systems -- Particle in Central Field -- Perturbations to Energy Levels.-Spin and Magnetic Field -- Electromagnetic Transitions -- Composite Systems and Identical Particles -- Applications to Atomic Physics.
Keywords: Physics; Quantum theory; Physics; Quantum Physics